2012
DOI: 10.1073/pnas.1210804109
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of pineal allopregnanolone in Purkinje cell survival

Abstract: It is believed that neurosteroids are produced in the brain and other nervous systems. Here, we show that allopregnanolone (ALLO), a neurosteroid, is exceedingly produced in the pineal gland compared with the brain and that pineal ALLO acts on the Purkinje cell, a principal cerebellar neuron, to prevent apoptosis in the juvenile quail. We first demonstrated that the pineal gland is a major organ of neurosteroidogenesis. A series of experiments using molecular and biochemical techniques has further demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
177
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(179 citation statements)
references
References 38 publications
2
177
0
Order By: Relevance
“…Therefore, the demonstration of pregnenolone formation from cholesterol is essential to establish de novo neurosteroidogenesis in the pineal gland. As an initial step in the demonstration of pregnenolone biosynthesis in the pineal gland, we found that cytochrome P450scc is expressed in the pineal gland of juvenile chickens [52] and juvenile quail [53] by reverse transcription polymerase chain reaction (RT-PCR) analysis (fig. 1).…”
Section: Biosynthesis Of Neurosteroids In the Pineal Glandmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the demonstration of pregnenolone formation from cholesterol is essential to establish de novo neurosteroidogenesis in the pineal gland. As an initial step in the demonstration of pregnenolone biosynthesis in the pineal gland, we found that cytochrome P450scc is expressed in the pineal gland of juvenile chickens [52] and juvenile quail [53] by reverse transcription polymerase chain reaction (RT-PCR) analysis (fig. 1).…”
Section: Biosynthesis Of Neurosteroids In the Pineal Glandmentioning
confidence: 99%
“…However, recent studies carried out in chickens [52] and quail [53] have demonstrated that the pineal gland, an endocrine organ located close to the brain, actively synthesizes neurosteroids de novo from cholesterol via pregnenolone (fig. 1).…”
Section: Biosynthesis Of Neurosteroids In the Pineal Glandmentioning
confidence: 99%
See 3 more Smart Citations